Romanian University Historians in the 1930s and 1940s - the Case of Dimitrie Todoranu, Professor at the University of Cluj - Ana-Maria Stan (University Babes-Bolyai, 2019)
This study focuses on the complex topics of university history and academic strategy as they were seen in the late 1930s and early 1940s by a Romanian scholar, Dimitrie Todoranu. At the time a young psychologist and university member of staff, Todoranu held influential administrative positions, being appointed head of the University Office at the Romanian University of Cluj in 1934. Starting from that year, and throughout the Second World War, he reflected and published rather extensively on the characteristics, the "role and the essenceˮ of a university in Europe and in particular in Central and Eastern Europe. Using the evolution of the Romanian University of Cluj as a case study, Todoranu tried to define what a modern university should look like, what were the best relationships between students and professors, what the public significance of a university should be in the life of a (nation)state. Todoranu's works and ideas testify not only to a significant phase in the field of European higher education, but also represent an important and a less known episode / contribution to the history of universities in the 20th century Romania.